Bengt Holbek and the Study of Meanings in Fairy Tales - Vaz da Silva, Francisco (2000)
This paper argues that Bengt Holbek’s attempt to reduce all “marvelous” elements in fairy tales to real-world referents drastically conceals the dynamics of traditional symbolic representations underlying this narrative genre.